EUV lithography - Bakshi, Vivek (SPIE Press monograph, 2018)
Extreme ultraviolet lithography (EUVL) is the principal lithography technology aiming to manufacture computer chips beyond the current 193-nm-based optical lithography, and recent progress has been made on several fronts: EUV light sources, optics, optics metrology, contamination control, masks and mask handling, and resists. This book covers the fundamental and latest status of all aspects of EUVL in field. It thoroughly covers the current in-field version of EUVL plus related topics, including light sources, optics, mask, photoresists, contamination, imaging and scanners. In the nine years since SPIE Press published the first edition of EUVL Lithography, much progress has taken place in the development of EUVL as the choice technology for NGL. In 2008, EUVL was a prime contender to replace 193 nm based optical lithography in leading edge computer chipmaking, but not everyone was convinced at that point. Switching from 193 nm to 13.5 nm wavelengths was a much bigger jump than the industry had attempted before. It brought several difficult challenges in all areas of lithography - light source, scanner, mask, mask handling, optics, optics metrology, resist, computation, materials and optics contamination. These challenges have been effectively resolved, and several leading-edge chipmakers have announced dates, starting in 2018, for inserting EUVL into high-volume manufacturing.